Pediatric pharmacokinetic considerations and implications for drug dosing - Jovanović Marija; Vučićević Katarina (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2022)
Optimizing the dosing of medicines for pediatric patients in routine clinical practice and determining the dose for clinical trials is still a challenging task. Children differ from adults in their response to drugs due to inherent differences in pharmacokinetics and/or pharmacodynamics, and responses may also vary among pediatric patients of different ages. However, the greatest disparities compared to adult pharmacokinetic profiles are observed in children below 2 years of age. The maturation of the liver and the kidneys, as well as the variation in body composition, are considered to be the main sources of pharmacokinetic variability. Hence, besides specific pharmacodynamic features, understanding age-related changes in drug absorption, distribution, and elimination is fundamental for optimizing drug efficacy and avoiding toxicity. This paper summarizes the pharmacokinetic changes throughout the childhood, along with the effect of developmental changes on drug dosage calculation. In clinical practice, age and body weight-based dosing regimens are usually used. In spite of dosing recommendations based on age and/or body weight, variabilities in pharmacokinetics and pharmacodynamic response remain, implying a need to monitor patients and optimize the dosing regimen according to physiological characteristics, disease characteristics and therapy.